Comparing flip chart and video-based diabetes self-management education on self-care in patients with type 2 diabetes mellitus in primary care: A two-group pretest–posttest study in Indonesia - Tiara Rizkika Bella; Popi Sopiah; Rafika Rosyida (Jurnal Keperawatan, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) is a global concern managed in primary healthcare settings, including in Indonesia. Enhancing self-care skills is crucial for preventing complications and improving disease control. The effectiveness of various educational media in Diabetes Self-Management Education (DSME) programs requires further exploration.Objectives: This study aims to compare the effectiveness of diabetes management education using flipcharts and videos on improving self-care skills in T2DM patients at primary healthcare facilities.Methods: A quasi-experimental design with a two-group pre-test-post-test approach was used, with 30 purposively selected participants. The DSDCA instrument assessed the conditions before and after the intervention. Four education sessions were delivered, with one group using flipcharts and the other videos. Data analysis included the Shapiro-Wilk test for normality, paired t-test for within-group changes, and independent t-test for between-group differences.Results: Both groups showed significant improvement (p = 0.001), with the flipchart group’s average self-care score rising from 32.00 to 59.30, and the video group’s from 35.33 to 56.73. However, there was no significant difference between the groups (p = 0.077).Conclusions: Both flipcharts and videos significantly improved self-care skills, suggesting that low-cost, technology-based media are as effective as more expensive alternatives. These findings are particularly relevant for implementation in low- and middle-income countries, offering flexibility for primary care nurses to select appropriate educational media based on patient needs and resources.